2008
DOI: 10.1039/b813140f
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the LCST of poly(2-oxazoline)s by varying composition and molecular weight: alternatives to poly(N-isopropylacrylamide)?

Abstract: The cloud point of copolymers of 2-ethyl-2-oxazoline and 2-n-propyl-2-oxazoline could be tuned from 25 degrees C to 100 degrees C by varying molecular weight and composition; the reversibility and concentration dependence of the cloud points were evaluated to assess the potential of these copoly(2-oxazoline)s as alternatives to poly(N-isopropylacrylamide).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
338
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 364 publications
(364 citation statements)
references
References 43 publications
23
338
0
3
Order By: Relevance
“…The concentration dependence of the CP of the comb polymer follows the same trend as for linear pCPropOx (Figure 5b), which is in contrast to the concentration dependence of poly(2-oxazoline)s with different cloud points due to different side chains, such as pEtOx and pnPropOx. 15 This confirms that the side-chains shield the MA backbone and that only the OCPropOx side-chains interact with the aqueous environment, resulting in similar LCST behavior for the linear and comb pCPropOx. However, the CP's of the comb polymer are decreased by ∼10°C when compared to linear pCPropOx, which may be a result of the large number of ÀCH 3 end groups at the pendant side chains of the comb structure as well as the high local polymer concentration.…”
Section: ' Results and Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…The concentration dependence of the CP of the comb polymer follows the same trend as for linear pCPropOx (Figure 5b), which is in contrast to the concentration dependence of poly(2-oxazoline)s with different cloud points due to different side chains, such as pEtOx and pnPropOx. 15 This confirms that the side-chains shield the MA backbone and that only the OCPropOx side-chains interact with the aqueous environment, resulting in similar LCST behavior for the linear and comb pCPropOx. However, the CP's of the comb polymer are decreased by ∼10°C when compared to linear pCPropOx, which may be a result of the large number of ÀCH 3 end groups at the pendant side chains of the comb structure as well as the high local polymer concentration.…”
Section: ' Results and Discussionsupporting
confidence: 65%
“…With the increase in concentration, the CP decreases in a nonlinear way and only a small decrease is observed when the concentration is increased from 10 to 30 mg mL À1 indicating that the CP at 30 mg mL À1 approaches the LCST value (Figure 5b). Both the DP and concentration dependence of the CP follow the same trend as for pnPropOx, 15 which is a consequence of the Type I FloryÀHuggins miscibility behavior that is characterized by a shift of the LCST toward lower polymer concentration when the polymer chain length is increased. 34 The CP of pCPropOx (30°C) lies in between the CP of pnPropOx (44°C) and piPropOx (27°C) (all 5 mg mL À1 and a DP of 100, ESI).…”
Section: ' Results and Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…The bisalkynelinked PNIPAM that was designed as no end-group effect reference gave the smallest molecular weight dependence among the three series studied here. As mentioned above, previous studies of PNIPAM and other thermoresponsive polymers have demonstrated the LCST to be independent [32][33][34]45], directly dependent [10,26], or inversely dependent [17,[27][28][29][30][31]46,47] upon polymer molecular weight. LCSTs are expected to be decreased with increasing molecular weight on the basis of the changes in the polymer-solvent interaction [48,49].…”
Section: Thermoresponsivity Of Pnipams Before and After Click Reactionmentioning
confidence: 98%